The proto‐oncogene ERG is a target of microRNA miR‐145 in prostate cancer. (8th April 2013) - Hart, Martin; Wach, Sven; Nolte, Elke; Szczyrba, Jaroslaw; Menon, Roopika; Taubert, Helge; Hartmann, Arndt; Stoehr, Robert; Wieland, Wolf; Grässer, Friedrich A.; Wullich, Bernd
<x xml:space="preserve">Abstract</x> Prostate cancer is a leading cause of cancer mortality in men. One of the distinct characteristics of prostate cancer is over‐expression of the ERG proto‐oncogene. The TMPRSS2–ERG gene fusion, the most common gene fusion, is found in approximately 50% of prostate cancer cases. We show that certain microRNAs are extensively deregulated in prostate cancer cell lines and primary clinical cancer samples. MicroRNAs are capable of modulating post‐transcriptional gene expression via inhibition of protein synthesis. Independent target prediction methods have indicated that the 3′ untranslated region of the ERG mRNA is a potential target of miR‐145. miR‐145 is consistently down‐regulated in prostate cancer. Here we show that the ERG 3′ untranslated region is a regulative target of miR‐145 in vitro. Ectopic expression of miR‐145 led to a reduction in expression of the ERG protein. We analyzed 26 prostate cancer samples and corresponding normal tissue. ERG protein expression was found to be elevated in the tumor samples, together with increased expression of several ERG isoforms. We identified ERG proteins of 35 and 24 kDa, which may represent unknown ERG splice variants. Analyses of miR‐145 and ERG mRNA expression revealed a general down‐regulation of miR‐145 irrespective of the presence or absence of translocations involving ERG. This observation indicates that down‐regulation of miR‐145 may contribute to the increased expression of most ERG splice variants sharing the miR‐145 target sequence in their 3′ untranslated region.